ACTUAL PROBLEMS OF LEGAL CULTURE - G. R. Absattarov, (Academic Journal of Physical and Chemical Sciences, 2019)
The article deals with the actual problems of legal culture, which have not yet been studied in the political science of Kazakhstan. The article examines in more detail the issues of system–political characteristics of Kazakhstan's legal culture, the principles and priorities of the legal culture of Kazakhstan society. The system of principles of legal culture of Kazakhstan can include only those provisions, which reveal the main, essential in its content. As the priorities of the legal culture of the Republic of Kazakhstan can be recognized only such fairly generalized guidelines that would be equally important for the law and policy, legal policy and legal culture of Kazakhstan as a whole, and for each of its separate areas of legal culture in the field of political and legal regulation. At the same time, the article focuses on the discussion issues.